Clinical outcomes of Najuta thoracic stent graft system for arch aneurysms - Iida, Yasunori; Hachiya, Takashi; Oka, Hidetoshi; Inaba, Yu; Miki, Takahisa; Shimizu, Hideyuki (Frontiers in Surgery, 2023)
Objectives We aimed to elucidate the perioperative and short-term clinical outcomes of the Najuta thoracic stent graft system with fenestrations for supra-aortic vessels. Methods We retrospectively investigated the perioperative and short-term clinical outcomes of 20 patients treated for arch or distal arch aneurysms using the Najuta thoracic stent graft system during the period from May 2019 to February 2023. Results The technical success rate of the Najuta thoracic stent graft system was 95%. Of the 20 patients, 17 patients (85.0%) underwent concomitant extra-anatomical supra-aortic bypass. Postoperative CT revealed type Ia (n = 2) and type II (n = 3) endoleaks which disappeared on follow-up. The postoperative complications were stroke (n = 2, 10.0%), paraplegia (n = 1, 5.0%), and paraparesis (n = 1, 5.0%). In a very old patient, a blood transfusion was performed from the common iliac artery using the retroperitoneal approach. There were no aorta-related complications such as retrograde type A dissection or distal stent graft–induced new entry. Conclusions We treated arch or distal arch thoracic aneurysms by inserting a tube-type stent graft as a scaffold on the peripheral site and placing the Najuta thoracic stent graft on the proximal site. By extending the landing zone to Zone 0 and using a low radial force, which is a feature of the Najuta thoracic stent graft system, postoperative bird-beak and aorta-related complications were avoided. The treatment of arch and distal arch aortic aneurysms using the Najuta thoracic stent graft system showed acceptable perioperative and short-term clinical outcomes. Thoracic endovascular aortic repair using the Najuta thoracic stent graft system may be a potential treatment option for arch and distal arch aortic aneurysms, warranting further studies.